2017
DOI: 10.48044/jauf.2017.001
|View full text |Cite
|
Sign up to set email alerts
|

Street Tree Diversity in Three Northeastern U.S. States

Abstract: Street tree diversity is widely viewed as a key component in the resilience of street tree populations to pests, diseases, and climate change. Assessment of street tree diversity is considered integral to sustainable street tree management and preservation of the ecosystem services and social benefits that street trees provide. This paper assesses street tree diversity in three northeastern U.S. states—New Jersey, New York, and Pennsylvania— by analyzing municipal street tree inventory data stratified by the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
1
15
0
1
Order By: Relevance
“…Street tree diversity has been assessed at a variety of geographic levels. It has most commonly been assessed at the level of the individual municipality (Cowett, Bassuk, 2017). Sjöman et al (2012) assessed street tree diversity in 10 Nordic cities, and Kendal et al (2014) assessed global street tree diversity from 108 cities in six continents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Street tree diversity has been assessed at a variety of geographic levels. It has most commonly been assessed at the level of the individual municipality (Cowett, Bassuk, 2017). Sjöman et al (2012) assessed street tree diversity in 10 Nordic cities, and Kendal et al (2014) assessed global street tree diversity from 108 cities in six continents.…”
Section: Discussionmentioning
confidence: 99%
“…The species richness by the Margalef index in the sanitary zones of industrial enterprises in Zaporozhye city was significantly lower (1.49-3.68) (Sklyarenko, Bessonova, 2019). In all the studies, deficiencies were found in street tree diversity on using a variety of metrics (Cowett, Bassuk, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A lower J' indicates low evenness or the dominance of a small number of species. While both the Shannon and Simpson diversity indices have been used to evaluate diversity of urban trees, we focused on the Simpson index because it is sensitive to evenness which is considered a desirable characteristic of urban forests (Cowett and Bassuk 2017). The Simpson index is sometimes reported as the Inverse Simpson Diversity Index (ISDI) for ease of interpretation since a high ISDI indicates high diversity (Sun 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, maples (Acer spp.) accounted for nearly 39% of the aggregated population across the tree inventories in those tree states (Cowett and Bassuk 2017). Maples also dominate in Toronto, Ontario, and other Canadian cities, due in part to political symbolism of maples in Canada (Vander Vecht and Conway 2015;Roman et al 2018).…”
Section: The Problem Of Low Urban Tree Diversitymentioning
confidence: 99%